Language Variation of The Word Play on The PPKM Abbreviation by Indonesian Netizen: A Sociolinguistic Study - Inda Syartanti, Nadya; Pristina Pidada, Ida Ayu (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
This study aims to reveal the form and function of the word play on the PPKM abbreviation created by Indonesian netizens in sociolinguistic studies. The data source taken from various of the online mass media articles such as Pikiran Rakyat and Tribun News that have collected various word plays on the PPKM abbreviation. The data collected through the observation method with note-taking techniques. The data were analyzed based on various forms of word play such as phonological, morphemic, phrasal, and graphic, and also analyzed based on their function as a form of anger, jokes, satire, or romance. The results show that the 40 data of the word play on the PPKM abbreviation contains various things, both in terms of structure and in terms of function. In terms of structure, various forms of lingual structure can be seen in phonological, morphemical, syntactical, and semantical terms. In phonology, the words used are a form of conversation that is often used by speakers in an informal environment. In morphemical, these words are selected and used regardless of the structure to adjust the equivalent of each letter in the PPKM abbreviation. In syntactical, the grammatical form of the word play on PPKM abbreviations is dominated by phrasal, especially noun phrases. In semantics, the word play on the PPKM abbreviation can be seen from the word meaning and the clause meaning, where each meaning is adjusted to the conditions of the speakers. In addition, in terms of function, the word play on the PPKM abbreviation is dominated by functions with negative nuances, namely bad romance which is aimed at limitations in carrying out romantic relationships due to PPKM , the function of sadness is aimed at people's lives at large due to not being able to move freely as usual, and the function of negative satire aimed at the government and authorized officials as a satire because the rules imposed have made people's lives increasingly unstable